RJX Improves Wound Healing in Diabetic Rats - Uckun, Fatih M.; Orhan, Cemal; Tuzcu, Mehmet; Durmus, Ali Said; Ozercan, Ibrahim H.; Volk, Michael; Şahin, Kazım (Frontiers Media Sa, 2022)
BackgroundWe recently reported the clinical safety profile of RJX, a well-defined intravenous GMP-grade pharmaceutical formulation of anti-oxidant and anti-inflammatory vitamins as active ingredients, in a Phase 1 study in healthy volunteers (ClinicalTrials.gov Identifier: NCT03680105) (Uckun et al., Front. Pharmacol. 11, 594321. 10.3389/fphar.2020.594321). The primary objective of the present study was to examine the effects of GMP-grade RJX on wound and burn injury healing in diabetic rats. MethodsIn the present study, a rat model of T2DM was used that employs HFD in combination with a single injection of STZ intraperitoneally (i.p) at a moderate dose level (45 mg/kg). Anesthetized diabetic rats underwent full-thickness skin excision on the back or were subjected to burn injury via a heated brass probe and then started on treatments with normal saline (NS = vehicle) or RJX administered via intraperitoneal injections for three weeks. FindingsNotably, diabetic rats treated with the 1.25 mL/kg or 2.5 mL/kg RJX (DM+RJX groups) rapidly healed their wounds as fast as non-diabetic control rats. Inflammatory cell infiltration in the dermis along with fibrin and cell debris on the epithelial layer persisted for up to 14 days in the DM+NS group but not in RJX-treated groups. The histopathological score of wound healing on days 7 and 14 was better in diabetic rats treated with RJX than diabetic rats treated with NS and comparable to the scores for non-diabetic healthy rats consistent with an accelerated healing process. The residual wound area of RJX-treated rats was significantly smaller than that of NS-treated diabetic rats at each evaluation time point (P<0.001). The accelerating effect of RJX on diabetic wound healing was dose-dependent. We obtained similar results in the burn injury model. Our results demonstrate that RJX - at a dose level >10-fold lower than its clinical maximum tolerated dose (MTD) - accelerates the healing of excision wounds as well burn injury in diabetic rats.
Keywords: COVID-19; RJX; pharmacology; pharmacodynamics; vitamins; nutrients; nutraceuticals; inflammation